Glaucoma Optic Neuropathy Progression: the Results of Long-Term Follow-Up - N. I. Kurysheva; V. N. Trubilin; E. O. Shatalova; L. V. Lepeshkina (Oftalʹmologiâ, 2019)
Purpose: to investigate the average speed and risk factors for the glaucomatous optic neuropathy (GON) progression during longterm observation. Patients and methods. The 10-year data of 750 patients were analyzed. The average GON progression rate was calculated on the basis of perimetry and optical coherent tomography data. Further, according to inclusion and exclusion criteria 128 patients were included into the group of retrospective analysis. Resultes. The following risk factors were established: initial cornealcompensated IOP (IOPcc) > 23.6 mm Hg (AUC 0.7), IOPcc after 5 years > 19.8 mm Hg (AUC 0.83), age > 69.5 years (AUC 0.6), corneal hysteresis < 9.9 mm Hg (AUC 0.6) and retinal nerve fiber layer < 92 μm (AUC 0.6). Patients with pseudoexfoliation syndrome, and patients taking systemic calcium channel blockers (p = 0.01) also had the higher risk of GON progression. Its rate was lower in patients with arterial hypertension (p = 0.015), and in patients who received prostaglandin analogues (risk was 5 times reduced, p = 0.04) and fixed combinations (risk was 2 times reduced, p = 0.018). IOPcc of higher than 17.6 mm Hg in the long-term period is the most pronounced risk factor for the progression of GON. It was determined that the average ROP of glaucoma progression among the patients was 0.6 dB/year for ROP1, 0.62 ± 1.09 μm/year for ROP2 and 0.95 ± 3.28 μm/year for ROP3, also each 1 dB/year decrease in photosensitivity (in group with glaucoma progression) was associated with further loss of RNFL (3.9 µm/year). Conclusion. The use of prostaglandin analogues and fixed combinations reduces this risk.